Analyzing the Use of Klik XYZ Application by Members of Koperasi XYZ with the Binary Logistic Regression Method - Syarah, Irra Siti; Heikal, Jerry (Universitas Pahlawan Tuanku Tambusai, 2024)
Advances in technology and the internet allow users to conduct transactions through mobile applications, including bill payments and product purchases. Koperasi XYZ has developed the Klik XYZ application to improve the efficiency and convenience of its members in shopping. This study aims to analyze the factors that influence the use of Klik XYZ application by cooperative members using binary logistic regression method. The variables analyzed include age, gender, frequency of access, and customer satisfaction. The analysis results show that age, gender, and customer satisfaction have a significant influence on purchasing decisions. The binary logistic regression model built has an overall accuracy rate of 89.3%, with a prediction accuracy of 90.7% for purchase behavior and 87.6% for non-purchase behavior. The findings can be used by XYZ to develop more effective marketing strategies by targeting members based on their age, gender, and satisfaction level. In addition, improving service quality and user experience can increase customer satisfaction, which in turn can increase purchase rates. By implementing the right marketing strategy, it is expected to improve XYZ's sales performance in the future and assist the cooperative in providing optimal service to its members.